Experimental Research on Material and Mechanical Properties of Rock-Like Filling Materials in Disaster Prevention of Underground Engineering - Junwei Shi; Zhangliang Chen; Binbin Zheng (Advances in Materials Science and Engineering)
Rock-like materials can be used as a filling material to improve the stability of underground engineering substantially. And the optimization of the rock-like material is an effective way to improve the performance of the filling material. Firstly, the AHP-FUZZY comprehensive optimization model was constructed for the complexity and fuzziness of the rock-like filling material ratio optimization. Secondly, according to the mechanical properties of rock-like filling materials under special environment (such as high temperature, high humidity, high stress, and high airtight) in old goaf, mechanical properties of rock-like filling materials were studied with the method of field core and laboratory test, which revealed the variation law of mechanical properties with time, and the regression equation between mechanical parameters and time was established with the method of least squares. Finally, the strength and deformation characteristics of rock-like filling materials were monitored by the monitoring and early warning technology. The results show that the optimal ratio of the rock-like filling materials is “E3”; that is, the cement content is 9%, the ash ratio is 2 : 5, and the mass concentration is 74%. The mass concentration is the main factor that affects the slump of the slurry, and the proportion of fly ash and coal gangue content directly affects the stratification and bleeding rate of the slurry. Reasonably increasing the ash and gangue ratio can significantly improve the workability and water retention of the rock-like filling materials. Also, the amount of composite cementitious material is the main factor that affects the setting time and the strength of the rock-like material. What is more, the special environment in gob is good for each chemical reaction fully in rock-like filling materials and strengthens the gelling property of deformation resisting capability, which can be a benefit for disaster prevention of underground engineering.